Enjoying Goal-Directed Action: The Role of Regulatory Fit - Freitas, Antonio L.; Higgins, E. Tory (Psychological Science, 2002)
We propose that the fit between an action's strategic orientation and the actor's regulatory state can influence the amount of enjoyment the action provides. In two studies using different methods of manipulating regulatory states and of gauging action evaluations, high regulatory fit increased participants' anticipations of action enjoyability. In a third study, high regulatory fit increased participants' enjoyment of, perceived success at, and willingness to repeat a novel laboratory task, and these effects were independent of participants' actual success on the task. Across the three studies, participants in a regulatory state oriented toward accomplishment experienced eagerness-related actions more favorably than vigilance-related actions, whereas participants in a regulatory state oriented toward responsibility experienced vigilance-related actions more favorably than eagerness-related actions. These findings' implications for understanding task interest and motivation are discussed.